The Influence of Promotion, Product Innovation, and Product Knowledge on Purchase Intention to Bakpia Jenang Product at CV Mubarokfood Cipta Delicia Kudus - Annisa Indra Kusuma; Putut - Haribowo; Budi - Prasetya (Politeknik Negeri Semarang, 2020)
Purchase intention was the stage where consumers make a choice among several products or brands included in a selection set, and in the end consumers will determine their choice to make a purchase of an item based on various considerations. The problem in CV Mubarokfood Cipta Delicia was purchase intention of Bakpia Jenang Product fluctuated which could be seen from the sales of Bakpia Jenang in 2019. Purchase intention can be influenced by several factors including promotion, product innovation, and product knowledge. This research aims to analyze the influence of promotion, product innovation, and product knowledge on purchase intention to Bakpia Jenang product at CV Mubarokfood Cipta Delicia Kudus. The sample consisted of 100 respondents. The data were collected by interview, questionnaire, and literature review. The analysis method was using multiple linear regression analysis by SPSS version 24,0. The result of this research stated that the promotion and product knowledge have significant effect on purchase intention to Bakpia Jenang product at CV Mubarokfood Cipta Delicia Kudus partially. While product innovation has no significant effect on purchase intention to Bakpia Jenang product at CV Mubarokfood Cipta Delicia Kudus partially. It can be seen in the result of t test in which t count > t table. The result of the promotion was 3,046 > 1,984 and the prduct knowledge was 8,475 > 1,984. While the innovation product was -0,975 < 1,984. Based on the result of determination coefficient test, the promotion, product innovation, and product knowledge have significant effect on purchase intention by 77,8%, meanwhile the rest of 22,2% was influenced by other factor.